Analisis Dampak Pencemaran Tanah Akibat Limbah Deterjen Terhadap Lingkungan Hidup Masyarakat Di Daerah Pedesaan - Bayu Sabilha Naufal; Dya Qurotul A’yun (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Soil pollution due to detergent waste is an increasingly worrying environmental problem, especially in rural areas. Detergent waste that is disposed of carelessly contains chemicals such as phosphates, surfactants and bleaching agents which can damage the soil ecosystem, disturb microorganisms and reduce soil quality. This research aims to analyze the impact of soil pollution due to detergent waste on the living environment of communities in rural areas. This research method uses literature study, which is a research approach using written sources to collect data. This research includes analysis of books, scientific journals, articles and other documents in order to gain an in-depth understanding of the topics discussed. The results of the research show that soil in rural areas exposed to detergent waste experiences a significant decline in quality, characterized by reduced soil fertility and disturbance. plant health. In addition, a correlation was found between the level of soil pollution and an increase in health problems among the population, such as skin diseases and respiratory problems. Public awareness of the dangers of detergent waste is still low, so educational efforts and the implementation of better waste management strategies are needed. This research emphasizes the importance of intervention from the government and environmental organizations to mitigate pollution and improve the welfare of rural communities.